Peningkatan Tanggung Jawab Diri Narapidana Melalui Layanan Konseling Realitas Di Lapas Kelas II A Banyuwangi - Ayu, Baiq Diyah; Yohandi; Sulaiman, A. Husam (CV. SINAR HOWUHOWU, 2025)
High recidivism rates among drug offenders indicate the need to reassess correctional interventions, particularly those addressing deficits in personal responsibility. Many prisoners deny their role in addictive behavior and attribute it to external factors. This study examines the effectiveness of Reality Therapy in strengthening personal accountability among inmates at Class IIA Banyuwangi Prison. Using a Single Instrumental Case Study design, the subject was WH (30 years old), a female narcotics offender with a history of minor recidivism and strong tendencies toward denial and self-justification. Data were collected through triangulated qualitative methods, including in-depth interviews, structured behavioral observation using a responsibility rubric, and document analysis. Findings reveal a significant transformation in the subject’s sense of responsibility. Prior to the intervention, the subject demonstrated a limited “Quality World” focused on short-term physical freedom and showed no personal accountability for her offense. A key cognitive shift occurred during the Evaluation stage of the WDEP model, where the subject recognized her behavior as a personal choice. Post-intervention, her responsibility score increased to 6/10, accompanied by more self-directed communication patterns. The study concludes that Reality Therapy is effective in fostering accountability by shifting the locus of control from external blame to conscious choice, highlighting its potential as a rehabilitation approach for drug offenders.